Theoretical and Numerical Research on V-Cut Parameters and Auxiliary Cuthole Criterion in Tunnelling - Xiaoming Lou; Bao Wang; En Wu; Mingwu Sun; Ping Zhou; Zhenchang Wang (Advances in Materials Science and Engineering)
This paper aims at providing a sound theoretical solution to auxiliary central hole and the cutting parameters. For this purpose, the forming mechanism of V-cut cavity for cutting blasting was performed based on the hypothetical rock breaking mechanism of V-cut blasting. A theoretical solution for increasing the critical depth of the auxiliary center cuthole and the criteria for increasing the cuthole diameter of various types of cutholes when the rock attributes, explosive properties, and cuthole dip angle are constant are proposed. (1) If charging length le < 0.75H/sin θ, no auxiliary cuthole is needed. (2) If 0.75H/sin θ < le < 0.75H/sin θ + (2∼4) × 0.1, a central vertical auxiliary hole is needed. (3) If 0.75H/sin θ + (2∼4) × 0.1 < le < 0.75(H/sin θ + Hi/sin θi), a shallow inclined hole is needed. (4) If le > 0.75(H/sin θ + Hi/sin θi), both the central vertical cuthole and the shallow inclined cuthole are needed. Meanwhile, the theoretical solution was verified by numerical modelling with ANSYS/LS-DYNA. Moreover, the field implementation of the V-cut and the auxiliary hole effectively improved the blasting effect in both efficiency and economy.